The Impact of Teaching Using TikTok on Improving Vocabulary Mastery of Highschool Students at SMAN 23 Makassar - Maria Clara Virginia Assi; Muliati Muliati; Asriati Asriati (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research was conducted to determine the effect of teaching using TikTok in improving students' vocabulary skills. The study used pre-experimental design. The sample was 34 11th-grade students using random cluster sampling technique. The researcher used a vocabulary test as an instrument based on several TikTok video contents that were taught. The vocabulary test was used as an instrument to find out the meaning of words, the use of words in context, and the parts of speech. This study conducted a pre-test to identify students' basic vocabulary abilities. In addition, the researcher provided treatment to achieve better vocabulary scores. Finally, a post-test was given to test the effect of teaching using TikTok in improving students' vocabulary skills. The pre-test and post-test scores were compared to see if teaching vocabulary using TikTok has an impact on improving students' vocabulary, and the data were analysed using a t-test. The results showed that the average pre-test score was 76.47, while the average post-test score was 91.76, indicating an increase. The paired sample t-test result was also significant, with a p-value of 0.000, which is lower than the alpha value of 0.05. It can be concluded that teaching using TikTok can improve the vocabulary mastery of students at SMAN 23 Makassar.Keywords: TikTok, Vocabulary Mastery